The 2dF-SDSS LRG and QSO Survey: The z<2.1 Quasar Luminosity Function from 5645 Quasars to g=21.85 - Richards, G; Croom, S; Anderson, S; Bland-Hawthorn, J; Boyle, B; Propris, R; Drinkwater, M; Fan, X; Gunn, J; Ivezic, Z; Jester, S; Loveday, J; et al. (2005)
We have used the 2dF instrument on the AAT to obtain redshifts of a sample of z<3, 18.0<g<21.85 (2000).="" (2004),="" (2qz)="" (2slaq).="" 105.7="" 2df="" 2df-sdss="" 2qz="" 2slaq="" 32%="" 5645="" a="" adopted="" agree="" al.="" algorithm="" all="" allow="" analysis,="" and="" are="" at="" beta="-1.45+/-0.03" boyle="" bright="" but="" consistent="" counts="" croom="" data="" deg^2.="" describe="" determinations="" end="" et="" faint="" final="" find="" fit="" for="" form="" from="" function="" functional="" g="" g\sim20.2.="" however,="" if="" imaging.="" in="" inconsistent="" is="" joint="" larger="" likelihood="" lrg="" luminosity="" maximum="" more="" normalization="" not="" number="" of="" only="" other="" our="" parameterization,="" parameters="" part="" preliminary="" present="" programme:="" qso="" quasar="" quasars="" redshift="" resulting="" results="" sdss="" selected="" selection="" slope="" steeper="" survey="" than="" the="" these="" to="" using="" vary="" vary.="" we="" well="" with="" yields="">21 deep surveys. The 2SLAQ data exhibit no well defined ``break'' but do clearly flatten with increasing magnitude. The shape of the quasar luminosity function derived from 2SLAQ is in good agreement with that derived from type I quasars found in hard X-ray surveys. [Abridged]</g<21.85>